Influence of Tunneling Incentive, Risk Management and Company Characteristics on Tax Avoidance with Corporate Social Responsibility Disclosure Asa Moderating Variable In Mining Companies Listed on IDX - Suripto - Suripto; Novitaria Novitaria (International Journal of Social Science and Business, 2021)
In Indonesia, there are tax evasion cases involving taxpayers paying taxes that must be paid in various ways. This gap phenomenon occurs in the case of a coal mining company that has been proven to have evaded tax. In addition, there are many more cases that show corporate tax evasion and have caused many state losses that impact the country's economic growth because of their efforts to reduce costs which are a source of income for the state. This study aims to provide empirical evidence of the effect of applying tunneling incentives, risk management, and firm characteristics using the leverage ratio and firm size, as independent variables, on tax avoidance as the dependent variable, with the use of Corporate Social Responsibility (CSR) as the independent variable. Variable moderator. Determination of the sample using the purposive sampling technique obtained a sample of 8 companies with 40 observational data. The analysis technique and hypothesis testing were carried out by panel data regression analysis through Eviews-11. The results showed that tunneling incentive and firm size had a significant positive effect on tax avoidance. Risk management and leverage do not affect tax avoidance. Corporate social responsibility can only moderate the effect of tunneling incentives on tax avoidance and firm size on tax avoidance but cannot moderate the effect of risk management and leverage.